Characterization and influence of hydroxyapatite nanopowders on living cells - Oberbek, Przemyslaw; Bolek, Tomasz; Chlanda, Adrian; Hirano, Seishiro; Kusnieruk, Sylwia; Rogowska-Tylman, Julia; Nechyporenko, Ganna; Zinchenko, Viktor; Swieszkowski, Wojciech; Puzyn, Tomasz (Beilstein Journal of Nanotechnology, 2018)
Nanomaterials, such as hydroxyapatite nanoparticles show a great promise for medical applications due to their unique properties at the nanoscale. However, there are concerns about the safety of using these materials in biological environments. Despite a great number of published studies of nanoobjects and their aggregates or agglomerates, the impact of their physicochemical properties (such as particle size, surface area, purity, details of structure and degree of agglomeration) on living cells is not yet fully understood. Significant differences in these properties, resulting from different manufacturing methods, are yet another problem to be taken into consideration. The aim of this work was to investigate the correlation between the properties of nanoscale hydroxyapatite from different synthesis methods and biological activity represented by the viability of four cell lines: A549, CHO, BEAS-2B and J774.1 to assess the influence of the nanoparticles on immune, reproductive and respiratory systems.
Keywords: nanomaterials safety; biomaterials; tissue engineering; microscopic characterization; cytotoxicity; hydroxyapatite